The role of menstrual cycle phase and AMH levels in breast cancer patients whose ovarian tissue was cryopreserved for oncofertility treatment - Takae, Seido (J Assist Reprod Genet, 2014)
PURPOSE: To determine the factors that affect oocyte extraction efficiency when using the “combined procedure”. In the present “combined procedure” ovarian tissue cryopreservation and oocyte extraction from an isolated ovary, later used in In Vitro Maturation (IVM), are performed concurrently. METHODS: Data were analyzed retrospectively and obtained from the clinical records of 27 young breast cancer patients referred for fertility preservation. RESULTS: The patients’ mean age was 33.7 (±3.8) years, mean serum anti-Müllerian hormone (AMH) concentration was 3.5 (±2.1) ng/ml, and mean number of extracted oocytes was 8.3 (±6.1). The phase of menstruation (follicular or luteal) did not affect either the number of oocytes extracted (P = 0.99) nor oocyte survival or maturation rates. Likewise, the number of oocytes that could be extracted was not affected by the type of laparoscopic procedure (multiple-port or single-incision laparoscopy; P = 0.94) or the molecular subtype of breast cancer (either Luminal A or B; P = 0.52). Analysis revealed that the number of extracted oocytes was well-correlated with the patient’s AMH serum level and age (coefficient of correlation: 0.60 and −0.48, respectively). CONCLUSION: We conclude that the outcome of the “combined procedure” primarily depends upon the patient’s serum AMH level and age. Importantly, the “combined procedure” may be used during any phase of the menstrual cycle to preserve the fertility of breast cancer patients.